ANSYS – A bibliometric study - Muhammad, Aisha; H. Ali, Mohammed A.; Shanono, Ibrahim Haruna
ANSYS is a general-purpose finite-element method tool deployed to numerically solve a wide range of engineering problems. Therefore, this paper presents a bibliometric analysis of research studies conducted using ANSYS. The work uses the Web of Science database to analyze the most active authors, institutions, countries and the most popular keywords used in the ANSYS research field. Based on the search phrase ‘‘Analysis using ANSYS” and ‘‘Analysis in ANSYS”, 359 articles were retrieved and they span between 1989 and 2019. Using bibliometric software (VOSviewer), graphical visualization of the bond between the authors, institutions, countries and keywords with bibliometric co-citations and collaborations were established. Based on the available data, it was found that Chinese and Indian authors are the most productive researchers in the field of ANSYS. This paper will assist industries, both old and new researcher with a keen interest in pursuing ANSYS related research to establish research collaborations or secure research funds from companies, government or individuals.